Reactivity of ground municipal solid waste incineration bottom ash as sustainable cement replacement: dominant control of initial particle size - Yongzhen Cheng; Weiye Mu (European Journal of Environmental and Civil Engineering, 2026)

An efficient lightweight XHP-CNN with multi-task adaptation for mango leaf disease recognition on mobile edge devices - Yi-Chen Chen; Jen-Cheng Wang; Mu-Hwa Lee; Yin-Hao Lai; Joe-Air Jiang (Computers and Electronics in Agriculture, 2026)

Surface-confined AlOxFy on thermal shock-generated α-Al2O3 for coke-resistant dehydrofluorination of 1,1-difluoroethane - Zhenxiang Li; Yongchao Zhao; Fengqing Hu; Zaizhe Cheng; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Ying Li; Wujian Zhang; Haodong Tang (Chemical Engineering Journal, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Unlocking the antioxidant potential of wheat gluten: structural transitions and peptide release driven by ultrasonication-assisted pH shifting - Peng Cheng; Xueying Song; Yihan Mu; Siliang Wu; Mouming Zhao; Guowan Su (Food Chemistry, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Low-temperature thermochemical energy storage behavior of Zn-doped phosphogypsum-based calcium sulfate dihydrate: Correlating defect evolution with electronic structure - Fei Mu; Shuai Luo; Meng Fu; Yuanyuan Li; Xuyuan Tang; Yaoqi Huang; Xiaomin Cheng (Chemical Engineering Journal, 2026)

Source-oriented ecological risk assessment and prioritization of heavy metals in soils impacted by coal gangue in Southwestern China - Guixiang Luo; Siyan Lv; Nan Mu; Yongmin Wang; Jiachun Lu; Cheng Zhang; Zhenwu Tang; Dingyong Wang (Applied Soil Ecology, 2026)

Airborne microplastics as concentrators of anthropogenic heavy metals: Differentiation of intrinsic additive-derived metals and post-emission enrichment - Wahyu Diah Proborini; Chun-Hsuan Wei; Chun-Hung Ku; Wei-Ting Hsu; Mu-Jean Chen; Hsiu-Chuan Chou; Yu-Cheng Chen (Journal of Hazardous Materials, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Sequence characterization and regulatory mechanisms of the EGFL7/miR-126b promoter in Larimichthys crocea - Yingying Cheng; Shuaiwei Ren; Yuan Zhang; Jingqun Ao; Xinhua Chen; Yinnan Mu (Fish & Shellfish Immunology, 2026)

Removal of acetaminophen and total nitrogen from secondary effluent via a UV/PAA-biofilter process: Efficiency, biofilm characteristics, and reaction mechanism - Kun’ao Du; Congwei Luo; Mingshan Yin; Ran Zou; Ning Guo; Yao Xu; Shiqi Bai; Xue Jiang; Xiaoxiang Cheng; Liping Qiu; Daoji Wu; Ruimin Mu (Environmental Research, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Wind Stress and Wind Disturbance Control Litterfall and Carbon Flux - Chen-Chia Ku; Sin Chen; Cheng-Yu Wu; Chun-Ping Huang; Bing-Mu Hsu; James A. Lutz; Wei-Chun Chao; Cheng-Wei Fan (Ecosystems, 2026)

Mitochondrial Communication Networks in the Bone Microenvironment: From the Maintenance of Homeostasis to Translational Interventions for Bone Diseases - Wentao Wang; Kun Wang; Wenjing Wang; Xuan Mu; Zhiquan Cheng; Guangzhi Zhang; Xuewen Kang; Yonggang Wang (Stem Cell Reviews and Reports, 2026)

Response of juvenile black rockfish (Sebastes schlegelii) to water temperature: Growth, antioxidant capacity, and metabolism - Xinting Mu; Qing Li; Zhiqiang Zhang; Xiaoqian Cheng; He Ma; Tomoaki Itayama; Rui Han; Yinghai Wu (Aquaculture International, 2026)

Decoding novel umami peptides from soy protein isolate hydrolysate: Mechanistic insights via multisensory techniques, machine learning and molecular docking - Xueying Song; Dipeng Mei; Yihan Mu; Peng Cheng; Siliang Wu; Chenchen Cao; Guowan Su (Food Bioscience, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Interaction between segmented lining and surrounding rock considering sliding layer for compressed air energy storage caverns - Liqi Mu; Yanshuo Hou; Lijuan Cheng; Caichu Xia; Chen Xu; Duofeng Cen; Ruixiang Chen; Angel Garcia-Fontanet Molina; Alfonso Rodriguez-Dono (Tunnelling and Underground Space Technology, 2026)

Engineering a 2-methylimidazole framework nanozyme for efficient oxidation of lactose to lactobionic acid under mild conditions - Donghui Xie; Yanna Jiao; Shaoyi Yu; Jia Tu; Yunhui Cheng; Xiaohong He; Daichen Mu; Keyu Xing; Zhou Xu (Journal of Environmental Chemical Engineering, 2026)

Comparison of nitrogen oxides (NO, NO2) analyzers from controlled conditions in a 100 m3 outdoor simulation chamber to field observations - Xuanming Huang; Xiaowei He; Jinzhao Tong; Baobin Han; Shichuan Ni; Zhiwei He; Xuelian Zhong; Xinmiao Xu; Min Cai; Yang Wang; Chenyang Xue; Wenya Niu; et al. (Journal of Environmental Sciences, 2026)

K isotope behavior in topsoil from the southeastern margin of the Tibetan Plateau - Yanan Cheng; Jun Mu; Peizheng He; Cheng Cao; Shichao An; Can Zhang; Xiaoping Feng; Cheng Zhao; Xiao-Ming Liu (Geochimica et Cosmochimica Acta, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Effects of Second-Order Wave Forces on the Extreme Response Estimation of the TLP Offshore Wind Turbine Under Multi-Directional Wind-Wave Loads - Jiahao Mu; Wei Shi; Linyang Cao; Jinghong Shang; Xu Han; Yang Yang; Liang Liu; Guangyuan Cheng (Journal of Marine Science and Engineering, 2026)
As offshore wind energy advances into deeper waters, the dynamic response and safety assessment of tension leg platform (TLP) wind turbines under complex marine conditions have become focal research points. This study investigates a 15 MW TLP wind turbine, acquiring data on motion responses, mooring tensions, and tower-base loads through time-domain analysis, with extreme value estimation conducted using the mean up-crossing rate method. The results indicate that under normal operating conditions, second-order wave forces significantly influence extreme response estimation. At an exceedance probability of 0.01, the second-order sum-frequency force increases the extreme tower base shear by 4.28% and the bending moment by 10.11% compared to the first-order-only case, while the difference-frequency force has a minor effect. Different wind-wave incidence angles cause distinct variations in turbine motion, with head-on incidence exciting the largest wave-frequency responses and lateral incidence producing relatively weaker excitation effects. Furthermore, the coupling effect between incident direction and second-order wave forces further amplifies extreme response risks. Therefore, it is essential to fully assess the prevailing wind-wave directions in the target sea area and consider the effects of second-order wave forces, especially the sum-frequency component, to ensure the long-term safe operation of TLP wind turbines under complex sea conditions.

Seeing Through the Waste: MD-YOLO for Precise Localization of Marine Debris - Hualin Mu; Minglin Yang; Cheng Yan; Jerome Yen; Neal N. Xiong (Journal of Marine Science and Engineering, 2026)
Marine ecosystem integrity is paramount to global stability. With the advancement of industrialization, various types of waste are discharged into the ocean, accumulating through the food chain and ultimately threatening human health and the global climate environment. To achieve precise and efficient cleanup of marine debris, traceability is essential, with detection and classification serving as critical steps. To address the issues of missed detection and occlusion caused by the irregular shapes of marine debris due to water pressure or structural characteristics, as well as the coexistence of multi-scale objects resulting from aggregation and shooting angles, this study proposes the MD-YOLO model based on the YOLOv11L architecture. Firstly, a deformable attention mechanism is introduced in the neck network to achieve dynamic sampling and precise localization of targets with imbalanced aspect ratios. Secondly, a context-aware multi-scale feature fusion module is embedded in the backbone network to effectively mitigate the issue of missed detection of small targets when objects of different sizes coexist. Finally, a cooperative spatial-channel attention mechanism is designed in the detection head to enhance the feature representation capability in visible regions and infer occluded areas, thereby significantly suppressing occlusion interference. Experiments conducted on a self-constructed dataset containing 5095 images demonstrate that the proposed method achieves 86.7% in mAP@0.5, 67.6% in mAP@0.5:0.95, and an F1 score of 0.83, significantly outperforming comparative methods. This study provides key technical support for the effective traceability of marine debris.

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Evaluating the performance of coastal virtual stations from different combinations of altimetry missions - Fukai Peng; Zhong He; Xiaoli Deng; Ole Baltazar Andersen; Dapeng Mu; Yunzhong Shen; Yanguang Fu; Xiao Cheng (Advances in Space Research, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Layered double hydroxides vs. metal-organic frameworks: Which enables more sustainable phosphate fertilizer production from sludge? - Xiaole Wang; Qian Zhao; Xiaoxiang Cheng; Jingtao Xu; Shujuan Meng; Yifan Zhao; Kechao Han; Ruimin Mu; Lei Liu (Journal of Environmental Chemical Engineering, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ultrasound-enhanced ferulic acid treatment modulates starch gel structure to inhibit retrogradation in rice starch during storage - Chen Tian; Yuxin Mu; Qianyu Hang; Xingbo Zhuang; Leiqing Pan; Cheng Zhang; Chao Ding; Qiang Liu (Journal of Stored Products Research, 2026)

pH-driven integrated impacts of the calcium sulfite/Fe(VI) system: In-depth insights into active species evolution and mechanisms - Kunyu Chen; Jie Wang; Xiaoxiang Cheng; Weikang Zhang; Jingwei Huang; Congwei Luo; Xinsheng Luo; Peijie Li; Yan Jin; Daoji Wu; Ruimin Mu; Jinsuo Lu (Journal of Hazardous Materials, 2026)

Corrigendum to “Comparative analysis of protein composition, digestion dynamics, and amino acid release between preterm infant formula and human milk: Implications for preterm infant formula optimization” [Food Res. Int. 227 (2026) 118124] - Yanchen Liu; Guangqing Mu; Xiaoyan Yang; Xian Cheng; Jingjing Kang; Xuemei Zhu (Food Research International, 2026)

Comparative analysis of protein composition, digestion dynamics, and amino acid release between preterm infant formula and human milk: Implications for preterm infant formula optimization - Yanchen Liu; Guangqing Mu; Xiaoyan Yang; Xian Cheng; Jingjing Kang; Xuemei Zhu (Food Research International, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

Minimal modification to displacement ventilation for significant improvement through air redistribution - Zi Cheng; Jingkai Wang; Zhenying Zhang; Hao Simone Wang; Yibin Lu; Zekai Mu; Jian Liu; Zhang Lin (Building and Environment, 2026)

Effects of dietary nanoplastics exposure on muscle quality, immunity, antioxidative capacity and digestive gland function of abalone (Haliotis discus hannai) - Jiping Zhang; Qiyuan Fu; Sisi Cheng; Hai Ren; Ye Mu; Jiahuan Liu (Aquatic Toxicology, 2026)

Bimetallic metal-organic frameworks with hydrolytic esterase activity applied to mycotoxin decontamination - Ke Cheng; Peiheng Dina; Fei Yu; Yinghui Zhang; Yunpeng Wang; Wenjing Mu; Xiuguo Wang (Chemical Engineering Journal, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Lithofacies Identification and Classification Based on Least Squares Support Vector Machine Optimized by Sparrow Search Algorithm - Chenyang Mu; Zhongjie Guo; Guangxu Wang; Xiaoxiao Zhang; Cheng Qian; Changsong Lin; Yang Chen; Yougong Wang; Wei Wu (Mathematical Geosciences, 2026)

Effect of water temperature on the depletion of enrofloxacin and its metabolite ciprofloxacin in largemouth bass (Micropterus salmoides) tissue following repeated oral administrations - Ruiqi Fan; Xinyue Wang; Yuanyuan Ren; Shuang Li; Wenfei Guo; Jiaqi Liu; Yingchun Mu; Xiaoyu Wang; Sudong Xia; Bo Cheng (Aquaculture, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Etched MOF-reinforced nanocellulose aerogels with hierarchical porosity for synergistic flame retardancy, thermal insulation, and self-cleaning - Jing Ren; Junfeng Peng; Mengmeng Guo; Jing Li; Zimeng Mu; Chunzu Cheng; Min Gao; Qun Li; Zhiqiang Li (Chemical Engineering Journal, 2026)

Integration of AD and pyrolysis for char fertilizer: Pyrolysis and nutrient characteristics of biogas residue at different fermentation degrees - Lan Mu; Kongyue Li; Yifan Wang; Biyu Wang; Zhanjun Cheng; Yunan Sun; Yingjin Song; Guanyi Chen (Biomass and Bioenergy, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Signaling pathways and potential therapeutic agents in trastuzumab-induced cardiotoxicity - Haonan Zhang; Changxu Lu; Siyuan Cheng; Jingyi Wu; Anqi Hu; Zhongyi Mu; Dan Dong; Mingli Sun (Apoptosis, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Numerical simulation on creep behavior of argillaceous siltstone under compression-shear coupling and humidity variations - Jiajun Ran; Bo Hu; Qiaohai Tan; Xianghe Ye; Yugang Cheng; Zhiqiang Lv; Mostafa Sharifzadeh; Mi Nie; Jian Mu; Wenbin Guo (Ocean Engineering, 2025)

Simultaneous removal of nitrate and ammonia at the sulfur/pyrite-microbe interface: A novel insight of pyrite in wastewater polishing treatment for nitrogen metabolism - Jianjun Luo; Cheng Hou; Zijun Wang; Ningyuan Gui; Yi-Xuan Wang; Xinbai Jiang; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

Structural modifications and physicochemical characterization of Pueraria lobata starch: Focusing on the impact of combined enzymatic and acid hydrolysis on emulsifying efficiency - Fang Fang; Shuyu Cheng; Lihua Huang; Zijing Tian; Haiyang Gao; Mingwei Mu; Yongjian Cai (Food Chemistry, 2025)

Health Risk Assessment and Source Identification of Dissolved Heavy Metal(loid)s in an Agricultural Basin of Chongqing, China - Xian Cheng; Yue Mu (Water, Air, & Soil Pollution, 2025)

Molecular characterization of a novel mitovirus and a botoulivirus coinfecting the fungus Nigrospora oryzae - Jinyue Zou; Lihong Cheng; Yitong Chen; Baojun Zhang; Fan Mu; Jichun Jia (Archives of Virology, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

Far-UVC photolysis of NaClO for iopamidol degradation: Role of reactive substances, degradation mechanisms and ecotoxicity - Yao Xu; Hongxiang Wang; Congwei Luo; Mingshan Yin; Xiaoxiang Cheng; Kunyu Chen; Yan Jin; Ruimin Mu; Jingtao Xu; Daoji Wu; Xuedong Zhai (Journal of Water Process Engineering, 2025)

Machine learning-accelerated determination of immunotoxicities of liquid crystal monomers - Jiawei Cheng; Yawen Yuan; Yunsong Mu; Fengchang Wu; Hyeong-Moo Shin; Christie M. Sayes; John P. Giesy (Journal of Hazardous Materials, 2025)

Distribution, ozone formation potential, and health risk assessments of VOCs in automotive seat cushion leather during finishing process - Zhaohui Yang; Chuanhui Mu; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Hazardous Materials, 2025)

Combined effects of Limosilactobacillus reuteri or Lactiplantibacillus plantarum strains with linoleic acid on alleviating inflammation and intestinal barrier dysfunction - Chunxue Jin; Cheng Guan; Jiang Yu; Tieqi Wang; Guangqing Mu; Yanfeng Tuo (Food Bioscience, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Mechanistic insights into enhanced volatile pyridine biodegradation through shortcut pyridine-N transformation in counter-diffusion biofilms by regulating biofilm stratification and microbial spatial interactions - Peng Zheng; Yan Li; Youpeng Cheng; Jing Wang; Yixuan Wang; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Influence of heterogeneous mixed-wettability evolution on different phases CO2 displacement and storage efficiency mechanisms: Based on pore structure characterization - Peizhai Cheng; Pingchuan Dong; Bingtao Yang; Youheng Zhang; Dongyang Ma; Junchang Mu; Zhenshuo Wang (Advances in Water Resources, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Particle size matters: Unraveling the impact of microplastic heteroaggregates on algal–bacterial consortium in wastewater treatment - Yan Jin; Xuqi Li; Xiaoxiang Cheng; Kunyu Chen; Ruimin Mu (Journal of Environmental Chemical Engineering, 2025)

Development of a CD3ε mAb that can identify and in vitro activate T cells in large yellow croaker (Larimichthys crocea) - Zhichao Fang; Yi Cao; Haokai Chen; Jie Cheng; Ming Geng; Jiong Chen; Yinnan Mu; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

Corrigendum to “Study the photocatalytic mechanism of the novel Ag/p-Ag2O/n-BiVO4 plasmonic photocatalyst for the simultaneous removal of BPA and chromium(VI)” [Chem. Eng. J. 361 (2019) 1352–1362] - Wei Zhao; Jin Zhang; Fengxia Zhu; Feihu Mu; Lili Zhang; Benlin Dai; Jiming Xu; Anfeng Zhu; Cheng Sun; Dennis Y.C. Leung (Chemical Engineering Journal, 2025)

A novel pre-oxidation of ultrafiltration membrane fouling mitigation via ascorbic acid-activated hydrogen peroxide - Yao Xu; Congwei Luo; Mingshan Yin; Xiaoxiang Cheng; Xinyu Zhang; Yan Jin; Ruimin Mu; Jingtao Xu; Kun'ao Du; Xue Jiang; Shiqi Bai; Daoji Wu; et al. (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Carbon encapsulated Fe0/Fe oxides for heterogeneous electro-Fenton process: Promoting Fe(II) regeneration under nanoconfinement - Kun-Xiao Zhang; Ablajan Tunyaz; Guan-Nan Zhou; Rong-Rong Ding; Pei-Wen Zheng; Xiao-Cheng Liu; Hou-Yun Yang; Yang Mu (Chemical Engineering Journal, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Behaviors of suction bucket foundations in sands under vertical tensile load and seismic action - Xinglei Cheng; Yuming Su; Kun Mu; Dechun Lu; Jianxin Zhang; Liqiang Sun (Soil Dynamics and Earthquake Engineering, 2025)

Screening of enzymes for bi-functional whey protein hydrolysates: virtual enzymolysis, fragmentomics, and molecular docking in silico - Ruoyun Gao; Fanhua Kong; Guangqing Mu; Xin Zhao; Jianbo Cheng; Fang Qian (Food Research International, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

Comparative Transcriptomic and Physiological Analyses Reveal Salt Tolerance Mechanisms of Beta vulgaris L - Ningning Li; Jiamin Cheng; Zijian Zhang; Yaqing Sun; Zhi Li; Yingnan Mu; Guolong Li (Sugar Tech, 2025)

Gradient purification of surface water and ultrafiltration membrane fouling mitigation based on Fe(VI) multifunctional integration characteristics: Is a sedimentation unit necessary? - Kunyu Chen; Jie Wang; Xiaojiang Huang; Ruimin Mu; Congwei Luo; Daoji Wu; Jing Liu; Jinsuo Lu; Xiaoxiang Cheng (Water Research, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Triple microenvironment synergy engineering by grain boundaries of hydrophilic Cu electrode for boosting low-concentration nitrate electroreduction - Xin Wang; Qinian Wang; Mu Yuan; Xu Cheng; Bo Zhang; Ke Zhang; Lili Wang; Chao Wu; Xing Zhang (Chemical Engineering Journal, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

Novel insights into the evolution of dissolved organic matter during different full-scale advanced treatment processes for textile secondary effluent - Cheng Cheng; Chuanyang Liu; Jian Shen; Siting Wang; Xiaojin Wu; Qiuran Xiong; Hongmei Mu; Bingliang Zhang; Jing Wu (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Study on Acoustic Emission-Resistivity Response of Hydraulic Fracturing in Rock-Like Samples - Jisheng Sui; Lianchong Li; Wenqiang Mu; Jian Lu; Liming Liu; Cheng Gu (Rock Mechanics and Rock Engineering, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Electronic-ionic dual-conductive framework/channel stabilized Zn anodes for high-performance aqueous Zn-ion batteries - Qian He; Zekai Zhang; Hongchun Mu; Cheng Lian; Quan Li; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2025)

Pantothenic acid alleviates osteoarthritis progression by inhibiting inflammatory response and ferroptosis through the SIRT1/Nrf2 signaling pathway - Yi Liu; Yang Wang; Shengqi Cheng; Jie Mu; Guanchen Yin; Hang Gao (Chemico-Biological Interactions, 2025)

Facilitating Fe2+ regeneration via biochar to activate peroxydisulfate for pollutants removal: Degradation mechanism and quantitative structure-activity relationship model - Bowen Yang; Zhengyi Fan; Dongqi Mu; Qiang Ma; Dunqiu Wang; Jian Wang; Longhui Zheng; Zhiwen Cheng; Jun Zhang (Journal of Environmental Chemical Engineering, 2025)

Diversity and dynamics of microbial communities during spontaneous fermentation of different cultivars of apples from China and their relationship with the volatile components in the cider - Jingyi Zhou; Xinyi Wang; Yonghao Cao; Yichao Cheng; Wenchao Li; Haibin Mu; Yanying Liang; Bin Tian; Xixi Zhao; Yuyang Song (Food Research International, 2025)

Barrierless reactions of C2 Criegee intermediates with H2SO4 and their implication to oligomers and new particle formation - Yang Cheng; Chao Ding; Tianlei Zhang; Rui Wang; Ruxue Mu; Zeyao Li; Rongrong Li; Juan Shi; Chongqin Zhu (Journal of Environmental Sciences, 2025)

Enhancing thermal conductivity, electromagnetic interference shielding, and joule heating in polyether ether ketone composites using three-dimensional scaly carbon fibre structures and structural optimisation - Yifan Wang; Fengyu Wen; Yashu He; Lin Cheng; Haoyuan Tan; Jierun Ma; Pengbo Lian; Yuxuan Gu; Rui Chen; Jianxin Mu (Chemical Engineering Journal, 2025)

A β-cyclodextrin-based supramolecular photonic crystal hydrogel biosensor with macroporous structures for naked-eye visual detection of cholesterol - Xi Wang; Jingjing Mu; Junjie Ren; Hairong Yu; Xingbin Lv; Ting Liang; Changjing Cheng (Carbohydrate Polymers, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

A comprehensive study on fermentation and aroma contributions of Torulaspora delbrueckii in diverse wine varieties: Insights from pure and co-fermentation studies - Yichao Cheng; Shijin Geng; Jin Zhang; Xixi Zhao; Jiao Jiang; Yanying Liang; Haibin Mu; Wenchao Li; Yi Qin; Yanlin Liu; Yuyang Song (Food Research International, 2025)

Regulation of oxygen vacancy by in-situ piezoelectric synthesized BiVO4 to induce spin polarization for boosting the piezo-photocatalytic activity - Ying Cheng; Tao Yu; Xuefei Lei; Biao Wang; Wenning Mu; Xuanwen Liu; Rui Guo (Chemical Engineering Journal, 2025)

Environmental behavior, toxic potencies, and risks of liquid crystal monomers: A critical review - Jiawei Cheng; Xiaojuan Li; Yawen Yuan; Mengxiao Wang; Yunsong Mu; Xiaoli Zhao; Fengchang Wu; John P. Giesy (Critical Reviews in Environmental Science and Technology, 2024)

Enhanced detection of mango leaf diseases in field environments using MSMP-CNN and transfer learning - Yi-Chen Chen; Jen-Cheng Wang; Mu-Hwa Lee; An-Chi Liu; Joe-Air Jiang (Computers and Electronics in Agriculture, 2024)

Acetylcholinesterase inhibitory phloroglucinols from tropic Rhodomyrtus tomentosa - Ling-Yun Chen; E-E Luo; Yu Pan; Cheng-Qin Liang; Mu-Yuan Yu; Xu-Jie Qin (Phytochemistry, 2024)

Effect of dynamic high-pressure microfluidization and thermal processing on quality and volatile components of NFC tomato juice - Zhiwei Zhang; Shuaixue Mu; Zhenhong Gao; Xinyi Yang; Meiyue Zhang; Yuying Cheng; Kunsheng Qu (Food and Bioproducts Processing, 2024)

Luteinizing Hormone Receptor Mutation (LHRN316S) Causes Abnormal Follicular Development Revealed by Follicle Single-Cell Analysis and CRISPR/Cas9 - Chen Zhang; Yongqiang Nie; Bufang Xu; Chunlan Mu; Geng G. Tian; Xiaoyong Li; Weiwei Cheng; Aijun Zhang; Dali Li; Ji Wu (Interdisciplinary Sciences: Computational Life Sciences, 2024)
Abnormal interaction between granulosa cells and oocytes causes disordered development of ovarian follicles. However, the interactions between oocytes and cumulus granulosa cells (CGs), oocytes and mural granulosa cells (MGs), and CGs and MGs remain to be fully explored. Using single-cell RNA-sequencing (scRNA-seq), we determined the transcriptional profiles of oocytes, CGs and MGs in antral follicles. Analysis of scRNA-seq data revealed that CGs may regulate follicular development through the BMP15-KITL-KIT-PI3K-ARF6 pathway with elevated expression of luteinizing hormone receptor (LHR). Because internalization of the LHR is regulated by Arf6 , we constructed LHR N316S mice by CRISPR/Cas9 to further explore mechanisms of follicular development and novel treatment strategies for female infertility. Ovaries of LHR N316S mice exhibited reduced numbers of corpora lutea and ovulation. The LHR N316S mice had a reduced rate of oocyte maturation in vitro and decreased serum progesterone levels. Mating LHR N316S female mice with ICR wild type male mice revealed that the infertility rate of LHR N316S mice was 21.4% (3/14). Litter sizes from LHR N316S mice were smaller than those from control wild type female mice. The oocytes from LHR N316S mice had an increased rate of maturation in vitro after progesterone administration in vitro. Furthermore, progesterone treated LHR N316S mice produced offspring numbers per litter equivalent to WT mice. These findings provide key insights into cellular interactions in ovarian follicles and provide important clues for infertility treatment. Graphical Abstract

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Dual-sensing nano-yarns for real-time pH and temperature monitoring in smart textiles - Yunlei Yin; Cheng Guo; Qianqian Mu; Wanwan Li; Hongying Yang; Yin He (Chemical Engineering Journal, 2024)

Preparation, structural properties, and in vitro and in vivo activities of peptides against dipeptidyl peptidase IV (DPP-IV) and α-glucosidase: a general review - Xinxin Mu; Rongchun Wang; Cuilin Cheng; Ying Ma; Yingchun Zhang; Weihong Lu (Critical Reviews in Food Science and Nutrition, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Ammonia monooxygenase-mediated cometabolic biotransformation of volatile 4-chlorophenol in nitrifying counter-diffused biofilms: A combined molecular dynamics simulation, DFT calculation and experimental study - Peng Zheng; Wenqiang Li; Yan Li; Youpeng Cheng; Jing Wang; Yang Mu; Jinyou Shen (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Continuous flow hydrothermal synthesis of MoVNbTeOx in micro-coil tubular reactor for oxidative dehydrogenation of ethane - Yuxin Chen; Yuting Wu; Shuairen Qian; Zhengwen Li; Changyan Xu; Ruiqi Du; Yao Mu; Tianying Dai; Binhang Yan; Yi Cheng (Chemical Engineering Journal, 2024)

Suppressing leakage current and charge accumulation via perovskite interface morphology regulation for efficient light-emitting diodes - Yongjian Chen; Xiankan Zeng; Cheng Yan; Shiyu Yang; Lunyao Pan; Chenglong Li; Maolin Mu; Wen Li; Guanqi Tang; Weiqing Yang (Chemical Engineering Journal, 2024)

Complete genome sequence of a novel mitovirus isolated from the phytopathogenic fungus Alternaria alternata causing apple leaf blotch - Jichun Jia; Hanyang Liang; Lihong Cheng; Jinsheng Xia; Xu Chen; Baojun Zhang; Fan Mu (Archives of Virology, 2024)

Foreign multinational enterprises pose hidden environmental pressures on China - Ao Liu; Cheng Chen; Yuxin Wen; Qijian Mu; Haoming Li; Li Chai (Journal of Cleaner Production, 2024)

Preparation, taste characterization, and evaluation of oyster composite products with increased umami and salty - Baifeng Fu; Shuzhen Cheng; Xin Zhang; Junjie Yi; Zhishen Mu; Ming Du (Food Bioscience, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Synthesis of N-vinylcarbazole from acetylene by a continuous high-pressure liquid-phase process with inherent safety - Yao Mu; Jiahe Fan; Bozhao Chu; Siqing Zhong; Yi Cheng (Chemical Engineering Journal, 2024)

Akkermansia muciniphila Protects Against Antibiotic-Associated Diarrhea in Mice - Shenyin Liu; Suying Zhao; Zhiwei Cheng; Yilin Ren; Xinyi Shi; Jing Mu; Xiangyang Ge; Yuan Dai; Lei Li; Zhan Zhang (Probiotics and Antimicrobial Proteins, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

A continuous polymerase chain reaction 3D spiral microreactor capable of facile and on-demand fabrication - Qiushuang Yang; Wenchao Zhou; Huan Li; Jialing Huang; Zeyuan Song; Long Cheng; Yihui Wu; Deqiang Mu (Analytica Chimica Acta, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Evolution rules of coal mesopore structure under the action of hydraulic coupling - Yanbin Yu; Ruoyu Mu; Weimin Cheng; Wenting Cui; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Source apportionment and predictable driving factors contribute to antibiotics profiles in Changshou Lake of the Three Gorges Reservoir area, China - Yue Mu; Bobin Tang; Xian Cheng; Yuanhang Fu; Weibin Huang; Jing Wang; Dewang Ming; Liangshu Xing; Jinzhong Zhang (Journal of Hazardous Materials, 2024)

Niche-specific modulation of long-chain n-alkanes degrading bacterial community and their functionality in forest habitats across the leaf litter-soil compartments - Bashir Hussain; Jung-Sheng Chen; Bing-Mu Hsu; Wei-Chun Chao; Cheng-Wei Fan (Applied Soil Ecology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Seismic response of tripod suction bucket foundation for offshore wind turbine in sands - Xinglei Cheng; Yang Li; Kun Mu; M. Hesham El Naggar; Yadong Zhou; Piguang Wang; Xiaohan Sun; Ju Liu (Soil Dynamics and Earthquake Engineering, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

Comparative evaluation of soybean meal vs. extruded soybean meal as a replacer for fishmeal in diets of olive flounder (Paralichthys olivaceus): Effects on growth performance and muscle quality - Nannan Shen; Zhicheng Song; Cancan Xia; Hua Mu; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Yongkai Sun; Chaoqing Wei; Lu Zhang (Aquaculture, 2024)

Enhanced azo dye reduction at semiconductor-microbe interface: The key role of semiconductor band structure - Hefei Shi; Xinbai Jiang; Xiaojiao Wen; Cheng Hou; Dan Chen; Yang Mu; Jinyou Shen (Water Research, 2024)

Suspect and nontarget screening of per- and polyfluoroalkyl substances based on ion mobility mass spectrometry and machine learning techniques - Hongxin Mu; Zhongchao Yang; Ling Chen; Cheng Gu; Hongqiang Ren; Bing Wu (Journal of Hazardous Materials, 2024)

Abundance, characteristics and risk assessment of microplastics in aquatic sediments: A comparative study in the Yellow River and Yellow Sea - Shuai Liu; Hairong You; Hongyu Mu; Jiaxin Cheng; Shaoping Kuang; Fayuan Wang; Hui Chen; Minggang Zheng; Yan Xu; Tao Liu (Waste Management, 2023)

Nano-biochar uptake and translocation by plants: Assessing environmental fate and food chain risk - Yuliang Li; Chenghao Ge; Cheng Cheng; Xiaolei Wang; Dunfeng Si; Chunyi Mu; Min Wang; Hongbo Li; Dongmei Zhou (Science of The Total Environment, 2023)

Heterostructured YFeO3/CeO2 as efficient photoelectrode for photoelectrochemical degradation of organic pollutants under visible light irradiation - Yen-Shen Kuo; Mu-Jung Lin; Cheng-Liang Hsu; Yi-Hung Liu (Journal of Water Process Engineering, 2023)

Oxalic acid-enhanced sulfamethoxazole degradation by V2O3/percarbonate process: Insights into the reactive oxygen species generation and conversion - Rui Liu; Mu-cheng Xu; Jin-yan Yang (Chemical Engineering Journal, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Foliar application of selenium nanoparticles alleviates cadmium toxicity in maize (Zea mays L.) seedlings: Evidence on antioxidant, gene expression, and metabolomics analysis - Min Wang; Chunyi Mu; Yuliang Li; Yixuan Wang; Wenyan Ma; Chenghao Ge; Cheng Cheng; Gaoling Shi; Hongbo Li; Dongmei Zhou (Science of The Total Environment, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Zincophile channel adjustment realizes dendrite-free zinc anode for low-temperature zinc-ion capacitors - Ming Sun; Zekai Zhang; Jin Chen; Yifan Zhang; Ruoyu Wang; Hongchun Mu; Cheng Lian; Wenqiang Wang; Gengchao Wang (Chemical Engineering Journal, 2023)

Prenatal PM2.5 exposure increases the risk of adverse pregnancy outcomes: evidence from meta-analysis of cohort studies - Wanrong Wang; Siqi Mu; Weizhen Yan; Naiyu Ke; Han Cheng; Rui Ding (Environmental Science and Pollution Research, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Isolation and characterization of tumorigenic bacteria associated with crown gall disease of Prunus humilis Bunge in China - Rong Xiao; Xiao-Peng Mu; Jian-Cheng Zhang; Shuai Zhang; Chun-Fen Zhang; Shu Deng; Jun-Jie Du; Peng-Fei Wang (European Journal of Plant Pathology, 2023)

Effect of hexavalent chromium exposure on the reproductive status and biomarker responses of female Geloina erosa - Hongling Mu; Gongsi Wang; Bo Huang; Xiangchao Fu; Sui Cheng; Jiao Wen (Ecotoxicology, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Optimizing microstructure of polyelectrolyte ion exchange membrane for electrodialysis - Jin Cheng; Weiyu Zhou; Meifeng Zhu; Zekai Zhang; Yijie Lu; Yakun Chen; Hongchun Mu; Cheng Lian; Honglai Liu (Chemical Engineering Journal, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

Experimental and numerical investigation of the dynamic responses of longline aquacultural structures under waves - Wenwan Cheng; Yuanyuan Xu; Ping Mu (Ocean Engineering, 2023)

Lumped variable representing the integrative effects of climate and underlying surface system: Interpreting Budyko model parameter from earth system science perspective - Changwu Cheng; Wenzhao Liu; Zhaotao Mu; Haixiang Zhou; Tingting Ning (Journal of Hydrology, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

Creating peroxidase-mimetic clusterzymes for efficient and selectively enzymatic diagnosis of biomarkers - Huang Zhu; Jiuhong Deng; Shengdong Mu; Sutong Xiao; Qian Li; Weiwen Wang; Yang Gao; Xianglin Luo; Shanshan Gao; Chong Cheng (Chemical Engineering Journal, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Artificial intelligence-aided preparation of perovskite SrFexZr1-xO3-δ catalysts for ozonation degradation of organic pollutant concentrated water after membrane treatment - Xu Wang; Yanan Zhang; Cheng Zhang; Huangzhao Wei; Haibo Jin; Zhao Mu; Xiaofei Chen; Xinru Chen; Ping Wang; Xiaoyan Guo; Fuchen Ding; Xiaowei Liu; et al. (Chemosphere, 2023)

Identification and characterization of diverse isomers of per- and polyfluoroalkyl substances in Chinese municipal wastewater - Hongxin Mu; Jiawei Wang; Ling Chen; Haidong Hu; Jinfeng Wang; Cheng Gu; Hongqiang Ren; Bing Wu (Water Research, 2023)

Predictive and estimation model of Cd, Ni, and Zn bioaccumulations in maize based on diffusive gradients in thin films - Rui Chen; Xiulin Mu; Jiaxing Liu; Nuo Cheng; Rongguang Shi; Miaomiao Hu; Zhuoran Chen; Hao Wang (Science of The Total Environment, 2023)

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

Short-term microbial effects on n-alkane during the early phase degradation and consequential modification of biomarkers in a lowland subtropical rainforest in southern Taiwan: A litterbag experiment - Bing-Mu Hsu; Jung-Sheng Chen; Tung-Yi Huang; Bashir Hussain; Wei-Chun Chao; Cheng-Wei Fan (Journal of Environmental Management, 2023)

Characterizing the spatiotemporal distribution of dissolved organic matter (DOM) in the Yongding River Basin: Insights from flow regulation - Yijuan Bai; Shurong Zhang; Enlin Mu; Yinjun Zhao; Lirong Cheng; Yi Zhu; Yumin Yuan; Yingying Wang; Aizhong Ding (Journal of Environmental Management, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Model development and validation of personal exposure to PM2.5 among urban elders - Wei-Ting Hsu; Chun-Hung Ku; Mu-Jean Chen; Chih-Da Wu; Shih-Chun Candice Lung; Yu-Cheng Chen (Environmental Pollution, 2023)

In-situ Fe/Ti doped amine-grafted silica aerogel from fly ash for efficient CO2 capture: Facile synthesis and super adsorption performance - Lingyuan Fan; Yuanqiong Mu; Jiali Feng; Fangqin Cheng; Mei Zhang; Min Guo (Chemical Engineering Journal, 2023)

Co-composting of cattle manure and wheat straw covered with a semipermeable membrane: organic matter humification and bacterial community succession - Yingjin Song; Ruiyi Li; Yuxin Wang; Yu Hou; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Lan Mu (Environmental Science and Pollution Research, 2022)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Impact of repeated intravenous infusions of umbilical cord–derived versus bone marrow–derived mesenchymal stem cells on angiogenesis in a pregnant experimentally induced deep venous thrombosis rat model - Xi Cheng; Weina Wang; Rong Du; Mu Zhang; Yuanyuan Xie; Weiwei Sun; Jingjing Ji; Baolan Sun; Yuquan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2022)

Assessing the effectiveness and function of the water resources tax policy pilot in China - Rulin Ouyang; Enlin Mu; Yibin Yu; Ying Chen; Jiangbo Hu; Haoran Tong; Zhe Cheng (Environment, Development and Sustainability, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

PheGRF4e initiated auxin signaling during moso bamboo shoot development - Miaomiao Cai; Wenlong Cheng; Yucong Bai; Changhong Mu; Huifang Zheng; Zhanchao Cheng; Jian Gao (Molecular Biology Reports, 2022)

Difructose anhydride III: a 50-year perspective on its production and physiological functions - Mei Cheng; Hao Wu; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2022)

Synthetic lethality in personalized cancer therapy - Ying Pang; Meng Cheng; Mu Chen; Kaijun Zhao; Yuanyuan Yin; Min Liu; Jing Zhang; Chunlong Zhong (Genome Instability & Disease, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Characterization of a newly identified RNA segment derived from the genome of Sclerotinia sclerotiorum reovirus 1 - Jichun Jia; Fan Mu; Yanping Fu; Jiasen Cheng; Yang Lin; Daohong Jiang; Jiatao Xie (Archives of Virology, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

Low-Se Diet Can Affect Sperm Quality and Testicular Glutathione Peroxidase-4 activity in Rats - Qin Wang; Shuo Zhan; Yiqun Liu; Feng Han; Lili Shi; Chao Han; Weipeng Mu; Jizhong Cheng; Zhen-wu Huang (Biological Trace Element Research, 2021)

Characterization of a novel botoulivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Fan Mu; Jichun Jia; Yunxiang Xue; Daohong Jiang; Yanping Fu; Jiasen Cheng; Yang Lin; Jiatao Xie (Archives of Virology, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Hyperprogressive disease in patients with advanced renal cell carcinoma: a new pattern of post-treatment cancer behavior - Zhong Zheng; Ke Wu; Zhixian Yao; Xingyu Mu; Hantao Wu; Weiguang Zhao; Leilei Cheng; Zhihong Liu (Immunologic Research, 2020)

Neuroprotective effects of miR-532-5p against ischemic stroke - Jingwei Mu; Xi Cheng; Shanshan Zhong; Xiaohong Chen; Chuansheng Zhao (Metabolic Brain Disease, 2020)

Mechanism of Water Inrush Through Fault Zones Using a Coupled Fluid–solid Numerical Model: A Case Study in the Beiyangzhuang Coal Mine, Northern China - Wenping Mu; Xiong Wu; Ruochen Deng; Qian Hao; Cheng Qian (Mine Water and the Environment, 2020)

FGF21 Protects Dopaminergic Neurons in Parkinson’s Disease Models Via Repression of Neuroinflammation - Xingxing Fang; Jinyu Ma; Dengcai Mu; Bing Li; Bolin Lian; Cheng Sun (Neurotoxicity Research, 2020)

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

TMT-based quantitative proteomics revealed follicle-stimulating hormone (FSH)-related molecular characterizations for potentially prognostic assessment and personalized treatment of FSH-positive non-functional pituitary adenomas - Ya Wang; Tingting Cheng; Miaolong Lu; Yun Mu; Biao Li; Xuejun Li; Xianquan Zhan (EPMA Journal, 2019)

Implementation of the Land Surface Processes into a Vector Vorticity Equation Model (VVM) to Study its Impact on Afternoon Thunderstorms over Complex Topography in Taiwan - Chien-Ming Wu; Hsiao-Chun Lin; Fang-Yi Cheng; Mu-Hua Chien (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Engineering properties of loess stabilized by a type of eco-material, calcium lignosulfonate - Guo-yu Li; Xin Hou; Yan-hu Mu; Wei Ma; Fei Wang; Yu Zhou; Yun-cheng Mao (Arabian Journal of Geosciences, 2019)

Genetic mapping of powdery mildew resistance genes in soybean by high-throughput genome-wide sequencing - Bingzhi Jiang; Mu Li; Yanbo Cheng; Zhandong Cai; Qibin Ma; Ze Jiang; Ruirui Ma; Qiuju Xia; Gengyun Zhang; Hai Nian (Theoretical and Applied Genetics, 2019)

Three new biflavonoids from the branches and leaves of Cephalotaxus oliveri and their antioxidant activity - Shu Xiao; Zhen-Qiang Mu; Chun-Ru Cheng; Jie Ding (Natural Product Research, 2019)

Source discrimination of mine water inrush using multiple methods: a case study from the Beiyangzhuang Mine, Northern China - Qiang Wu; Wenping Mu; Yuan Xing; Cheng Qian; Jianjun Shen; Yang Wang; Dekang Zhao (Bulletin of Engineering Geology and the Environment, 2019)

Permafrost warming along the Mo’he-Jiagedaqi section of the China-Russia crude oil pipeline - Fei Wang; Guo-yu Li; Wei Ma; Yun-cheng Mao; Yan-hu Mu; Mihaela Serban; Yong-jun Cai (Journal of Mountain Science, 2019)

Coralloluteibacterium thermophilus sp. nov., A Gammaproteobacterium Isolated from an Oil Reservoir - Jing You; Shan Hong; Jiliang Yu; Lisha Duan; Bo Liu; Bozhong Mu; Cheng Zhou; Yanfen Xue (Current Microbiology, 2018)

The complete maternal mitochondrial genome sequence of Cuneopsis heudei (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lu Ma; Lin Li; Ruijuan Feng; Huan Mu; Xin Wang; Cheng Wang; Xuepeng Wang (Conservation Genetics Resources, 2018)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

Estimation of groundwater discharge and associated chemical fluxes into Poyang Lake, China: approaches using stable isotopes (δD and δ18O) and radon - Fu Liao; Guangcai Wang; Zheming Shi; Guoqiang Cheng; Qingmin Kong; Wenqing Mu; Liang Guo (Hydrogeology Journal, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Fine-mapping of QTLs for individual and total isoflavone content in soybean (Glycine max L.) using a high-density genetic map - Zhandong Cai; Yanbo Cheng; Zhuwen Ma; Xinguo Liu; Qibin Ma; Qiuju Xia; Gengyun Zhang; Yinghui Mu; Hai Nian (Theoretical and Applied Genetics, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Evaluation of pulsed corona discharge plasma for the treatment of petroleum-contaminated soil - Rui Li; Yanan Liu; Ruiwen Mu; Wenyan Cheng; Stéphanie Ognier (Environmental Science and Pollution Research, 2017)

Ecological effects of rice-duck integrated farming on soil fertility and weed and pest control - Qing Teng; Xue-Feng Hu; Chang Cheng; Zhiqing Luo; Fan Luo; Yong Xue; Yijun Jiang; Zhen Mu; Liming Liu; Minyong Yang (Journal of Soils and Sediments, 2016)

Thermal and spectral characterization of anaerobic thermal behavior patterns in a lacustrine sediment core - Fei Guo; Yunsong Mu; Cheng Chen; Haiqing Liao; Yingchen Bai (Environmental Science and Pollution Research, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Genome-wide analysis of shoot growth-associated alternative splicing in moso bamboo - Long Li; Tao Hu; Xueping Li; Shaohua Mu; Zhanchao Cheng; Wei Ge; Jian Gao (Molecular Genetics and Genomics, 2016)

A characterization of grapevine of GRAS domain transcription factor gene family - Xin Sun; Zhengqiang Xie; Cheng Zhang; Qian Mu; Weimin Wu; Baoju Wang; Jinggui Fang (Functional & Integrative Genomics, 2016)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Ectopic WWOX Expression Inhibits Growth of 5637 Bladder Cancer Cell In Vitro and In Vivo - Gang Li; Longfeng Sun; Zhongyi Mu; Yan Huang; Cheng Fu; Bin Hu (Cell Biochemistry and Biophysics, 2015)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Derivation of marine water quality criteria for metals based on a novel QICAR-SSD model - Cheng Chen; Yunsong Mu; Fengchang Wu; Ruiqing Zhang; Hailei Su; John P. Giesy (Environmental Science and Pollution Research, 2015)

A Potential Association Between Antibiotic Abuse and Existence of Related Resistance Genes in Different Aquatic Environments - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Tien-Yu Chang; Po-Min Kao; Shao-Feng Tseng; Tsung-Yu Shen; Feng-Cheng Shih; Cheng-Wei Fan; Jorn-Hon Liu (Water, Air, & Soil Pollution, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Therapeutic radionuclides in nuclear medicine: current and future prospects - Chai-Hong Yeong; Mu-hua Cheng; Kwan-Hoong Ng (Journal of Zhejiang University-SCIENCE B, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Metal Pollution (Cd, Pb, Zn, and As) in Agricultural Soils and Soybean, Glycine max, in Southern China - Yunyun Zhao; Xiaolong Fang; Yinghui Mu; Yanbo Cheng; Qibin Ma; Hai Nian; Cunyi Yang (Bulletin of Environmental Contamination and Toxicology, 2014)

Molecular cloning and expression analysis of glutathione peroxidase and glutathione reductase from Gracilaria lemaneiformis under heat stress - Ning Lu; Yan Ding; Xiao-Nan Zang; Xue-Cheng Zhang; Hao Chen; Xiao-Sheng Mu (Journal of Applied Phycology, 2013)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Effects of intercropping sugarcane and soybean on growth, rhizosphere soil microbes, nitrogen and phosphorus availability - Xiuping Li; Yinghui Mu; Yanbo Cheng; Xinguo Liu; Hai Nian (Acta Physiologiae Plantarum, 2013)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Complete nucleotide sequence of a Chinese isolate of Grapevine leafroll-associated virus 3 reveals a 5′ UTR of 802 nucleotides - Fei Fei; Mu-Di Lyu; Jie Li; Zai-Feng Fan; Yu-Qin Cheng (Virus Genes, 2013)

Rural tourism development in China: Principles, models and the future - Ling-en Wang; Sheng-kui Cheng; Lin-sheng Zhong; Song-lin Mu; Bijaya G. C. Dhruba; Guo-zhu Ren (Journal of Mountain Science, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Phylogeny of Celastrus L. (Celastraceae) inferred from two nuclear and three plastid markers - Xian-Yun Mu; Liang-Cheng Zhao; Zhi-Xiang Zhang (Journal of Plant Research, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

A linkage map of cultivated cucumber (Cucumis sativus L.) with 248 microsatellite marker loci and seven genes for horticulturally important traits - Han Miao; Shengping Zhang; Xiaowu Wang; Zhonghua Zhang; Man Li; Shengqi Mu; Zhouchao Cheng; Ruowei Zhang; Sanwen Huang; Bingyan Xie; Zhiyuan Fang; Zhenxian Zhang; et al. (Euphytica, 2011)

Molecular characterization and NF-κB-regulated transcription of selenoprotein S from the Bama mini-pig - Ningbo Zhang; Wenqian Jing; Jiayue Cheng; Wentao Cui; Yulian Mu; Kui Li; Xingen Lei (Molecular Biology Reports, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Study on regional production and economy of cobia Rachycentron canadum commercial cage culture - Cheng-Ting Huang; Sha Miao; Fan-Hua Nan; Shi-Mu Jung (Aquaculture International, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Physicochemical evolution and positive selection of the gymnosperm matK proteins - Da Cheng Hao; Jun Mu; Shi Lin Chen; Pei Gen Xiao (Journal of Genetics, 2010)

Molecular phylogeny, long-term evolution, and functional divergence of flavin-containing monooxygenases - Da Cheng Hao; Shi Lin Chen; Jun Mu; Pei Gen Xiao (Genetica, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Lipopolysaccharide upregulates uPA, MMP-2 and MMP-9 via ERK1/2 signaling in H9c2 cardiomyoblast cells - Yi-Chang Cheng; Li-Mien Chen; Mu-Hsin Chang; Wei-Kung Chen; Fuu-Jen Tsai; Chang-Hai Tsai; Tung-Yuan Lai; Wei-Wen Kuo; Chih-Yang Huang; Chung-Jung Liu (Molecular and Cellular Biochemistry, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Magnification of Flood Disasters and its Relation to Regional Precipitation and Local Human Activities since the 1980s in Xinjiang, Northwestern China - Jiang Fengqing; Zhu Cheng; Mu Guijin; Hu Ruji; Meng Qingxia (Natural Hazards, 2005)

Using the Flow Cytometry to Quantify the Giardia Cysts and Cryptosporidium Oocysts in Water Samples - Bing-Mu Hsu; Nan-Min Wu; Hung-Der Jang; Feng-Cheng Shih; Min-Tao Wan; Chien-Min Kung (Environmental Monitoring and Assessment, 2005)

Temporal and spatial expression of biologically active human factor VIII in the milk of transgenic mice driven by mammary-specific bovine α-lactalbumin regulation sequences - Chuan-Mu Chen; Chih-Hong Wang; Shinn-Chih Wu; Chih-Cheng Lin; Shwu-Hwa Lin; Winston T.K. Cheng (Transgenic Research, 2002)